Design of Structure Bionic Crab-Like Robot based on Gear Transmission - Qin Huibin; Zheng Zhizhen; Liu Yulong; Wang Min; Wang Kai (Jixie chuandong)
Based on the physiological characteristics of crab,a bionic crab- like robot composed of eight legs and two pincers is designed by using bionics principle. The cross direction moving and turning of the bionic crab- like robot are realized by controlling the walk stepping motor to drive gear crank connecting rod mechanism,the lifting and falling of pincers is realized by controlling the lifting stepping motor to drive gear and rack mechanism,the left and right swing of pincers is realized by controlling the swing steering engine,the snatching of pincers is realized by controlling the snatching steering engine drive intermittent gear and double- rocker linkage mechanism. The bionic crab robot has three good merits such as agile transmission,high driving efficiency,convenient maintaining,which is seasoned with different road surface. The robot has a good application potential under complex road conditions to search and detection. The design method is helpful for transmission design of multi- legged bionic robot in execrable environment.